Europe PMC in 2017. Issue Volume 46:Issue D1(2018) (17th November 2017) - Levchenko, Maria; Gou, Yuci; Graef, Florian; Hamelers, Audrey; Huang, Zhan; Ide-Smith, Michele; Iyer, Anusha; Kilian, Oliver; Katuri, Jyothi; Kim, Jee-Hyub; Marinos, Nikos; Nambiar, Rakesh; et al.
Abstract: Europe PMC (https://europepmc.org ) is a comprehensive resource of biomedical research publications that offers advanced tools for search, retrieval, and interaction with the scientific literature. This article outlines new developments since 2014. In addition to delivering the core database and services, Europe PMC focuses on three areas of development: individual user services, data integration, and infrastructure to support text and data mining. Europe PMC now provides user accounts to save search queries and claim publications to ORCIDs, as well as open access profiles for authors based on public ORCID records. We continue to foster connections between scientific data and literature in a number of ways. All the data behind the paper - whether in structured archives, generic archives or as supplemental files - are now available via links to the BioStudies database. Text-mined biological concepts, including database accession numbers and data DOIs, are highlighted in the text and linked to the appropriate data resources. The SciLite community annotation platform accepts text-mining results from various contributors and overlays them on research articles as licence allows. In addition, text miners and developers can access all open content via APIs or via the FTP site.